Konstruksi Sistem Ekonomi Islam Dalam Pemikiran Muhammad Baqir Al-Sadr - Abdul Hamid (Al Mashaadir : Jurnal Ilmu Syariah, 2021)
The "standard framework" for an economic system is an absolute necessity. In Islamic economics, the process of finding a "standard framework" has generated debate and has spawned several schools of economics. One of the earliest to offer an Islamic economic framework in the modern era was Muhammad Baqir al-Sadr. In this paper, we want to study in depth how the construction of Islamic economic thought offered by al-Sadr. The data analysis method used hermeneutic method. The results of this study conclude that Islamic economics is not a science but a school. The concept of ownership in Islamic economics consists of three components, namely: individual ownership, joint ownership, and Muslim ownership. Justice is the main goal, and to achieve it, distribution must be carried out in two stages, namely pre-production distribution and post-production distribution.